High-resolution study of the 3D collagen fibrillary matrix of Achilles tendons without tissue labelling and dehydrating - Wu, Jian-Ping; Swift, B.; Becker, Thomas; Squelch, Andrew; Wang, A.; Zheng, Y.; Zhao, X.; Xu, J.; Xue, W.; Zheng, M.; Lloyd, D.; Kirk, Brett (Wiley-Blackwell, 2017)
Â© 2017 The Authors Journal of Microscopy Â© 2017 Royal Microscopical Society Knowledge of the collagen structure of an Achilles tendon is critical to comprehend the physiology, biomechanics, homeostasis and remodelling of the tissue. Despite intensive studies, there are still uncertainties regarding the microstructure. The majority of studies have examined the longitudinally arranged collagen fibrils as they are primarily attributed to the principal tensile strength of the tendon. Few studies have considered the structural integrity of the entire three-dimensional (3D) collagen meshwork, and how the longitudinal collagen fibrils are integrated as a strong unit in a 3D domain to provide the tendons with the essential tensile properties. Using second harmonic generation imaging, a 3D imaging technique was developed and used to study the 3D collagen matrix in the midportion of Achilles tendons without tissue labelling and dehydration. Therefore, the 3D collagen structure is presented in a condition closely representative of the in vivo status. Atomic force microscopy studies have confirmed that second harmonic generation reveals the internal collagen matrix of tendons in 3D at a fibril level. Achilles tendons primarily contain longitudinal collagen fibrils that braid spatially into a dense rope-like collagen meshwork and are encapsulated or wound tightly by the oblique collagen fibrils emanating from the epitenon region. The arrangement of the collagen fibrils provides the longitudinal fibrils with essential structural integrity and endows the tendon with the unique mechanical function for withstanding tensile stresses. A novel 3D microscopic method has been developed to examine the 3D collagen microstructure of tendons without tissue dehydrating and labelling. The study also provides new knowledge about the collagen microstructure in an Achilles tendon, which enables understanding of the function of the tissue. The knowledge may be important for applying surgical and tissue engineering techniques to tendon reconstruction.